HARGA DIRI DAN INTERAKSI SOSIAL DITINJAU DARI TINGKAT PENDIDIKAN ORANG TUA PADA SISWA SMA NEGERI 7 PEKANBARU - Mesant, Repapul; Rosmawati, Rosmawati; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Self esteem is an evaluation of an individual done by themselves which can be either positive or negative. People with positive self esteem has good social interaction whereas those with negative self esteem lack in this department. As for parent’s role in the development of teenager’s self esteem, a family has an important role in developing a child’s personality. This research aims to find out a student’s self esteem and their social interactions in regards of the education levels of the parents. As for the indicators of self esteem include self respect/appreciation and appreciation from others. The indicators of social interactions involve cooperation, adjustment, competition, and communication. The method used in this research is descriptive qualitative. Based on the result of the research with 121 students of SMA Negeri 7 Pekanbaru as the sample, it can be seen that the student’s self esteem in regards of the education levels of the parents is categorized as high coming from those with elementary school level which is 80%. The student’s social interactions in regards of the education levels of the parents of the SMA Negeri 7 Pekanbaru students are categorized as high as well, coming from those with elementary school level which 100%.Key word : Self-Esteem, Social Interaction, Parental education level